TIRTHA PENGENTAS SEBAGAI TEOLOGI PEMBEBASAN - I Wayan Sunampan Putra (Jnanasiddhanta : Jurnal Teologi Hindu, 2023)
Religion has a goal to achieve moksha. In achieving moksha, it is carried out in various ways which are commonly referred to as chess marga yoga. However, the interesting thing is that apart from the yoga aspect, the means of the ceremony are the most important thing in achieving moksha, one of which is tirtha pengantas. The alleviating tirta has the function of purifying the spirit. Departing from this, this paper raises the topic of tirtha pengantas as a theology of liberation. The data in this paper is qualitative data. The purpose of this paper is to describe the tirtha of endorsing as a theology of liberation. Where it is also explained the meaning of tirtha penenttas, theology of liberation, and tirtha terpentas in the study of liberation theology. From this, it can be concluded that tirtha pengantas is the most important suggestion in Hinduism as a theology of liberation, namely freeing the atman from all attachments. Keywords: Tirtha Pengatas, Ngaben Ceremony, Liberation Theology